2016
DOI: 10.1111/eulj.12184
|View full text |Cite
|
Sign up to set email alerts
|

On The Odiousness of Greek Debt

Abstract: Unlike the popular narrative, which suggests that the Greek debt crisis was the result of lavish spending, this article demonstrates that the 'crisis' was generated by a transformation of purely private debt into public debt. This finding is supported by the preliminary report of the Greek Parliamentary Committee on the Truth of the Greek Debt, which clearly showed that the exponential increase of private debt in Greece risked the collapse of the private financial institutions exposed to it, namely Greek, Fren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The most sustained engagement with the TCPD has come from legal scholars who have recently shown that the Committee's arguments are well supported in international law and significantly challenge the Troika's narratives. 53 Others have used the findings outlined in the Preliminary Report to support their own claims about the illegitimacy of the debt. 54 Despite the TCPD's untimely demise, then, this body of scholarship ultimately affirms the value of engaging with the Committee's work as a legal strategy for sovereign debt cancellation, with implications beyond the immediacy of the Greek context.…”
Section: The Greek Truth Committee On the Public Debtmentioning
confidence: 99%
“…The most sustained engagement with the TCPD has come from legal scholars who have recently shown that the Committee's arguments are well supported in international law and significantly challenge the Troika's narratives. 53 Others have used the findings outlined in the Preliminary Report to support their own claims about the illegitimacy of the debt. 54 Despite the TCPD's untimely demise, then, this body of scholarship ultimately affirms the value of engaging with the Committee's work as a legal strategy for sovereign debt cancellation, with implications beyond the immediacy of the Greek context.…”
Section: The Greek Truth Committee On the Public Debtmentioning
confidence: 99%
“…Recent research affirming the legitimacy of the TCPD's arguments under international law (Bantekas & Vivien, 2016) affords a certain confidence in the central tenets of its approach, and as such raises the possibility of the model's appropriation, development, and transformation in future. In this sense, perhaps the legacy of 'Greek Debt Truth Commission' is to sketch out a terrain of struggle -memory -and a set of tools that are equal to it and may, someday, contribute to our escape from the debt economy.…”
Section: Conclusion: Failures and Legaciesmentioning
confidence: 99%
“…Although the TCPD was prematurely closed as a consequence of political schisms that opened up within SYRIZA (Toussaint & Lemoine, 2017: 34-53), legal scholars have recently shown that the arguments it developed are well supported in international law and significantly challenge the Troika's narratives regarding the debt from an economic, legal and political perspective (Bantekas & Vivien, 2016). Despite its untimely demise, the TCPD thus has much to offer in terms of legal strategy and practice regarding the cancellation of sovereign debt beyond the immediate context of the Greek crisis.…”
mentioning
confidence: 99%